Thermal Conductivity of Crumb Rubber as Partial Sand Replacement and Recycled Aggregates as Partial Coarse Aggregate Replacement in Concrete - Ramlan, Ridhuan; Shahidan, Shahiron; Zainol, Nor Najihah; Mohd Zuki, Sharifah Salwa (Springer Nature, 2020)
Disposal of waste tire rubber has become a major environmental issue worldwide and is increasing day by day, especially in Malaysia where carbon emission is among the highest in the world. Therefore, recycled waste materials are being used as construction materials in order to create new innovative products that are able to mitigate environmental pollution, reduce the cost of construction and improve the properties of concrete. This study discusses the utilisation of crumb rubber and recycled aggregates in concrete construction and the objective of this study is to determine the thermal conductivity of crumb rubber and compare the optimum strength of concrete materials. 12 cube samples measuring 200 200 100 mm containing different percentages of crumb rubber (0, 1, 2, 3, 4, and 5%) as fine aggregate substitute and 50% of recycled aggregates as coarse aggregate substitute were produced. The concrete grade used for these specimens is grade 35. The curing process was conducted on the samples to achieve the standard strength of concrete in 7 and 28 days. Therefore, the real strength of concrete was measured after the curing process. A slump test was conducted to determine the properties of crumb rubber. In addition, the samples were examined using the guarded hot box method to obtain the optimum percentage of crumb rubber as partial sand replacement in concrete for thermal conductivity. The results show that thermal conductivity (k-value) decreased slightly with the increase in crumb rubber content. However, the quality of concrete also slightly increased as the percentage of crumb rubber content increased. Lastly, based on the results, 5% of crumb rubber and 50% of recycled aggregates were suggested as the optimum percentages to be used in concrete as it achieved the lowest thermal conductivity compared to conventional concrete.